2011
DOI: 10.1016/j.neuron.2011.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Oscillations Mediate Directed Interactions between Prefrontal Cortex and Hippocampus of the Neonatal Rat

Abstract: The coactivation of prefrontal and hippocampal networks in oscillatory rhythms is critical for precise information flow in mnemonic and executive tasks, yet the mechanisms governing its development are still unknown. Here, we demonstrate that already in neonatal rats, patterns of discontinuous oscillatory activity precisely entrain the firing of prefrontal neurons and have distinct spatial and temporal organization over cingulate and prelimbic cortices. Moreover, we show that hippocampal theta bursts drive the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
302
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(341 citation statements)
references
References 59 publications
34
302
3
Order By: Relevance
“…Pregnant Wistar rats were obtained at 14 -17 d of gestation from the animal facility of the University Medical Center Hamburg-Eppendorf, housed individually in breeding cages with a 12 h light/dark cycle, and fed ad libitum. Extracellular recordings were performed in the PFC (2-2.5 mm anterior to bregma and 0.2-0.7 mm from the midline) and intermediate Hipp (3-4 mm posterior to bregma and 3-4 mm from the midline) of postnatal day 0 (P0) to P14 male rats (Ashwell and Paxinos at al., 2008) using experimental protocols as described previously Yang et al, 2009;Brockmann et al, 2011). Briefly, under light urethane anesthesia (0.5-1 g/kg; Sigma-Aldrich), the head of the pup was mounted into the stereotaxic apparatus (Stoelting) using two metal bars set in place with dental cement on the nasal and occipital bones, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pregnant Wistar rats were obtained at 14 -17 d of gestation from the animal facility of the University Medical Center Hamburg-Eppendorf, housed individually in breeding cages with a 12 h light/dark cycle, and fed ad libitum. Extracellular recordings were performed in the PFC (2-2.5 mm anterior to bregma and 0.2-0.7 mm from the midline) and intermediate Hipp (3-4 mm posterior to bregma and 3-4 mm from the midline) of postnatal day 0 (P0) to P14 male rats (Ashwell and Paxinos at al., 2008) using experimental protocols as described previously Yang et al, 2009;Brockmann et al, 2011). Briefly, under light urethane anesthesia (0.5-1 g/kg; Sigma-Aldrich), the head of the pup was mounted into the stereotaxic apparatus (Stoelting) using two metal bars set in place with dental cement on the nasal and occipital bones, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Fast events (gamma episodes in the PFC, gamma oscillations and ripples in the Hipp) superimposed on slow events were detected either automatically or by eye and confirmed by time-frequency plots. Spindle bursts (SB) and nested gamma spindle bursts (NG) were classified according to previously described criteria (Khazipov et al, 2004;Brockmann et al, 2011). The presence of short gamma episodes automatically detected after 30 -100 Hz filtering and confirmed by eye on at least onethird of the cycles in intermittent slow oscillations led to classification of these events as NG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, this type of plasticity was reported in the developing PFC, which facilitates the morphological and functional changes necessary to refine behaviorally relevant communication derived from hippocampal oscillatory activity (Brockmann et al, 2011). Although gene expression studies have been reported for neonatal marmoset hippocampus using marmoset-specific DNA microarray (Datson et al, 2009), we examined molecules whose expression has not been reported in wider regions such as the entorhinal (Ent) cortex.…”
Section: Dynamic Gene Expression In Efferent Regions Of the Pfc-hippomentioning
confidence: 98%
“…For example, numerous investigations of prefrontal and hippocampal circuits in both rodents and humans highlight the importance of theta (4-10 Hz) and gamma (32-150 Hz) rhythms and their interaction for the successful integration of both spatial and non-spatial information during goal-directed behaviors (Jones and Wilson, 2005;Sirota et al, 2008;Anderson et al, 2010;Benchenane et al, 2010;Hyman et al, 2010;Womelsdorf et al, 2010;Brockmann et al, 2011). These oscillatory rhythms emerge from interactions between excitatory glutamatergic and inhibitory GABAergic neurotransmission, which are in turn subject to behavior-dependent neuromodulation.…”
Section: Introductionmentioning
confidence: 99%